Kemiskinan Masyarakat Kawasan Hutan (Studi Pada Suku Kalende Di Kabupaten Buton Provinsi Sulawesi Tenggara) - La Ode Muhammad Deden Marrah Adil (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2013)
Poverty community forest is a classic problem that never completed. Poverty alleviation is actually the focus of development programs suistainable country and often exploited politically, especially without a clear realization of community empowerment. Therefore, it takes all the effort in a planned, integrated and systemic to enable these communities out of poverty. Data collection techniques used include observation, interviews, and documentation. The results of this study indicate that community empowerment through the development of agricultural/ plantation, human resource capacity building and coordination of functional institutions is absolutely necessary kemasyarakat Kalende tribal society. Thus, they can be detached from the rope noose of poverty that have binding Kalende tribal society